Study of the compressive strength of concrete block prisms : stack and running bond - Mohamad, Gihad (2011)
The main goal of this work is to investigate the nonlinear behavior of concrete block masonry prisms under compression, with an emphasis in the prism deformability and the failure modes. A total of 18 stack-bonded prisms have been tested, using hollow blocks of a single geometry and two different mortar types. To investigate the effect of vertical joints, the bond pattern – stack and running bond – in the prism was varied, by using half units. Finite element analysis of hollow masonry prisms was done utilizing a commercial non-linear finite element code DIANA. The numerical simulation were carried out using non-linear two dimensional 8-node elements and the biaxial stress state material was modeled by a combination of the yield conditions of Rankine and Drucker-Prager. The numerical and experimental results were compared to validate the ability to predict deformation and peak load. The results show that an analytical model cannot be formulated without understanding the interaction between block and mortar. It was observed that: the non-linearities of the masonry correspond to an increase in the lateral strain due to extensive cracking of the material and a progressive increase in the ratio between lateral and axial strains.; the cracks in the three block stacked prisms constructed with a stronger mortar were vertical on both sides; the prisms constructed with a weaker mortar had, as a consequence of localized crushing, also vertical cracks due to stress concentration at some points; the presence of a vertical joint in the prism led to the appearance of separation cracks between the middle block and the vertical mortar joint.